Freedom of choice, gender equality, or employment promotion? Finnish party positions on childcare in the light of election manifestos 2015. Issue 3 (3rd July 2017) - Nyby, Josefine; Nygård, Mikael; Autto, Janne; Kuisma, Mikko
Abstract: The principle of freedom of choice in childcare matters has been a central element of Finnish family policy since the 1980s and is something that makes the country unique in an international comparison. One the one hand, this principle has been manifested as a legislated right for parents, notably mothers, to choose paid work supported by the use of public childcare. On the other hand, it has also given parents with children under three the right to stay at home with their children and to receive a child home care allowance during this period. This dualism has been widely popular among parents and has also been seen by most leading parties as something that is good for families. However, since the outbreak of the international financial crisis, this system has faced increasing criticism from some experts and politicians, which has made the principle of freedom of choice, and especially the child home care allowance/leave, susceptible to renegotiation. This article investigates how the principle of freedom of choice was politicized by eight leading parties during the Finnish parliamentary election campaign in 2015, through an analysis of election manifestos. First, we analyse to what extent this principle was politicized, and by whom. Secondly, we study how the principle was framed. The findings show that the principle of freedom of choice was a rather politicized topic, creating a cleavage between conservative and leftist/liberal parties. Moreover, they indicate a renegotiation of this principle in favour of higher parental employment promotion and gender equality.